2019
DOI: 10.1016/j.jsxm.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Systematic Reviews and Meta-Analyses in Erectile Dysfunction Treatment and Management Published in the Sexual Medicine Literature

Abstract: Introduction Erectile dysfunction (ED) is a common medical condition that requires high-quality evidence to guide clinical practice; however, systematic reviews (SRs) and meta-analyses (MAs) often vary in quality, raising concerns regarding the validity of their results. Aim To perform an objective analysis of SRs and MAs in ED treatment and management and to report on the quality of published literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…It has been shown that AMSTAR scores for erectile dysfunction treatment systematic reviews have a "fair to good" quality. 26 The AMSTAR 2 items can be found in Table 2.…”
Section: Data Extractionmentioning
confidence: 99%
“…It has been shown that AMSTAR scores for erectile dysfunction treatment systematic reviews have a "fair to good" quality. 26 The AMSTAR 2 items can be found in Table 2.…”
Section: Data Extractionmentioning
confidence: 99%
“…The clinical efficacy and safety profile of PDE5i has been reported by numerous high-quality, well-designed, blinded, randomized controlled trials comparing PDE5i both to placebo and to other PDE5i drugs [3,4,5,6]. Overall, oral PDE5i in recommended doses is an effective medical therapy for ED with an excellent safety profile and is generally well tolerated.…”
Section: Current Standard Erectile Dysfunction Therapymentioning
confidence: 99%
“…Erectile dysfunction (ED) is defined as a persistent inability to obtain or maintain an erection for satisfying sexual intercourse. 1 Worldwide, up to 50% of men aged 40 to 70 years have ED. 2 An increasing amount of evidence shows that ED is caused by the interaction of multiple physiologic systems, such as endocrine, neural, and vascular systems.…”
Section: Introductionmentioning
confidence: 99%